Parental Bereavement and Academic Resilience in Indonesian Adolescents: Emotion Regulation as Mediator and Social Support as Protective Factor - Listaunsanti, Lynda Yenie; Setyawan, Jefri (Utan Kayu Publishing, 2025)
Parental bereavement represents one of the most profound emotional disruptions in adolescence, yet its academic implications remain underexplored, particularly in relation to how emotional regulation interacts with social support to sustain academic performance. This qualitative phenomenological study investigated the adaptive processes of two 18-year-old students in Surabaya who experienced parental loss, aiming to understand how they navigated grief while remaining engaged in learning. Data were collected through in-depth interviews and classroom observation, then analyzed using thematic analysis. Four themes emerged: academic resilience, emotion regulation, social support, and negative emotional experiences. Findings reveal that despite emotional disruptions and social stigma, both students demonstrated perseverance, reflective help-seeking, and meaning-making abilities, supported by cognitive reappraisal and culturally grounded coping (e.g., sabar, ikhlas, prayer). Emotion regulation served as a mediating mechanism linking bereavement to academic resilience, while peer and family support acted as protective buffers fostering motivation and emotional stability. Practically, this study underscores the need for grief-sensitive pedagogy and teacher training in emotional scaffolding to support bereaved students’ adjustment. Theoretically, the study extends Academic Resilience Theory (Cassidy, 2016) by positioning emotion regulation as a mediating mechanism and social support as a key protective factor in the context of parental loss. Abstrak: Kehilangan orang tua merupakan salah satu pengalaman emosional paling mendalam pada masa remaja, namun dampaknya terhadap capaian akademik masih belum banyak diteliti. Penelitian kualitatif dengan pendekatan fenomenologis ini mengeksplorasi proses adaptasi dua siswa berusia 18 tahun di Surabaya yang mengalami kehilangan orang tua, dengan tujuan memahami bagaimana mereka mengelola duka sembari tetap terlibat dalam proses pembelajaran. Data dikumpulkan melalui wawancara mendalam dan observasi kelas, kemudian dianalisis menggunakan analisis tematik. Empat tema utama ditemukan: resiliensi akademik, regulasi emosi, dukungan sosial, dan pengalaman emosional negatif. Hasil menunjukkan bahwa meskipun mengalami gangguan emosi dan stigma sosial, kedua peserta mampu menunjukkan ketekunan, perilaku pencarian bantuan yang reflektif, dan kemampuan memaknai pengalaman, yang didukung oleh reappraisal kognitif dan strategi koping berbasis budaya (misalnya sabar, ikhlas, dan doa). Regulasi emosi berperan sebagai mekanisme mediasi yang menghubungkan pengalaman kehilangan dengan resiliensi akademik, sementara dukungan dari teman sebaya dan keluarga berfungsi sebagai faktor protektif yang memperkuat motivasi dan stabilitas emosional. Secara praktis, temuan ini menegaskan pentingnya penerapan pedagogi sensitif-duka dan pelatihan guru terkait emotional scaffolding dalam mendukung proses adaptasi siswa yang berduka. Penelitian ini memperluas penerapan Academic Resilience Theory (Cassidy, 2016) dengan menempatkan regulasi emosi sebagai mekanisme mediasi dan dukungan sosial sebagai faktor protektif dalam konteks kehilangan orang tua.